2018
DOI: 10.3928/19425864-20180306-02
|View full text |Cite
|
Sign up to set email alerts
|

Athletic Trainers' Perceptions of Academic Adjustment Procedures for Student-Athletes With Concussion

Abstract: Purpose: To explore athletic trainers' perceptions of academic adjustments for student-athletes following a concussion. Methods:Sixteen secondary school athletic trainers selected via criterion-based and random purposeful sampling were interviewed via telephone. Inclusion criteria were: certified by the Board of Certification; completed the Beliefs, Attitudes, and Knowledge of Pediatric Athletes with Concussions survey; and had a minimum of 5 years of athletic trainer experience in the secondary school setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…A large array of responsible persons for RTL policy and accommodation development were cited, including teachers ( n = 4),63,91–93 physicians ( n = 3),89,94,95 athletic trainers/directors ( n = 3),63,79,83 school nurses ( n = 2),91,95 and SLPs ( n = 2) 80,96. In 9 studies, the Beliefs, Attitudes and Knowledge of Pediatric Athletes with Concussions (BACPAC) was used 85,97–103. This tool was developed to understand collaboration, perception of leadership, concussion management, referrals, and academic accommodations.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A large array of responsible persons for RTL policy and accommodation development were cited, including teachers ( n = 4),63,91–93 physicians ( n = 3),89,94,95 athletic trainers/directors ( n = 3),63,79,83 school nurses ( n = 2),91,95 and SLPs ( n = 2) 80,96. In 9 studies, the Beliefs, Attitudes and Knowledge of Pediatric Athletes with Concussions (BACPAC) was used 85,97–103. This tool was developed to understand collaboration, perception of leadership, concussion management, referrals, and academic accommodations.…”
Section: Resultsmentioning
confidence: 99%
“…Accommodations and management recommendations were primarily centered on linking students to resources,8 increasing concussion knowledge through education,89,91–93,114,115 decreasing stress,82,108 and increasing sleep/rest 82,108. The series of BACPAC survey studies found professionals agree accommodations are beneficial 85,97–103,106. Outside the BACPAC studies, 6 other articles developed surveys to assess benefits of accommodations 92,110,113–115.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations